A sociological analysis of the provision of extended studies as a means of addressing transformation at a historically white university - Tanyanyiwa, Precious (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
Foundation provisioning has a long history in South Africa, and is central to the transformation agenda, particularly the broadening of successful participation in higher education (HE). As access initiatives underpinned by various conceptualisations, foundation programmes evolved from peripheral, to semi-integrated and finally fully integrated curricular models in the form of current Extended Studies Programmes (ESPs). Underpinning the provision of Extended Studies is the acknowledgment that students who enter institutions are essentially ill equipped to cope with the demands of higher education studies, "leaving institutions themselves free of the responsibility of student failure" (Akoojee & Nkomo, 2007:391). This under-preparedness has been attributed to the 'articulation gap' between secondary and higher education, which in turn contributes to low retention and graduation rates (CHE, 2013:17). Situated within an overarching commitment to access and success, the Extended Studies Programme attempts to systematically address the 'articulation gap'. This study evaluated the extent to which the Rhodes University Humanities Extended Studies Programme is achieving its objectives from a transformation perspective, specifically the broadening of successful participation in higher education. The majority of previous works on the evaluation of foundation programmes focused on measurable dimensions of student access and success "“ that is retention and graduation rates. This thesis considered both the measurable outcomes of the programme as well as the actual teaching and learning process. Given the shifts that have taken place in foundation provisioning, the evaluation of the current model of foundation provisioning necessitated their location in history. Therefore, the evaluation of the Rhodes University Humanities Extended Studies Programme was undertaken in view of the shifts, achievements, challenges and critics of its predecessor programmes. Specifically, the following dimensions were considered in the evaluation of the programme: i) assumptions underpinning the design and purpose of the programme, ii) teaching and learning practices in the programme, iii) student and staff perceptions of the programme, iv) students' experiences of the programme, v) the validity of the programme in the broader institution, and vi) the measurable outcomes of the programme âˆ’ that is retention and graduation rates of students enrolled in the programme. The triangulation of qualitative data collection techniques provided access into the different layers of institutional relations, processes and structures, which not only affect teaching and learning in the programme, but also determine students' engagement with different academic and social aspects of the broader university. The theoretical insights of Pierre Bourdieu and Amartya Sen were integrated in order to provide analytical tools for both understanding the causes of inequalities in higher education, and evaluating institutional processes and structures that perpetuate or transform inequalities. Whilst Bourdieu's social reproduction thesis exposed the ways in which social structures shape educational processes and outcomes, Sen's capability approach provided tools for evaluating both institutional arrangements and individual capabilities "“ that is, the freedom to achieve desired educational outcomes (Sen, 1992:48).
Keywords: Rhodes University; Articulation (Education); Articulation (Education) -- South Africa -- Grahamstown; Educational equalization -- South Africa -- Grahamstown; Discrimination in education -- South Africa -- Grahamstown; Education, Higher -- South Africa -- Grahamstown; Bourdieu, Pierre, 1930-2002; Sen, Amartya, 1933-